Clístenes de Sición, el oráculo délfico y la primera guerra sagrada - Fornis, César (1991)
Este artículo estudia la relación entre el Oráculo Délfico y la dinastía Ortagórida, principalmente Clístenes de Sición. Este tirano intentó obtener el apoyo del santuario con su participación en la Primera Guerra Sagrada y la reorganización de los Juegos Píticos, pero en el siglo VI a. C. la actitud de la Pitia hacia la tiranía era de hostilidad, como sucedió también con los Pisistrátidas en Atenas y Polícrates en Samos durante el mismo siglo.
This paper studies the relation between the Delphic Oracle and the Orthagorid dinasty, principaly Cleisthenes of Sicyon. This tyrant tried to obtain the support of the shrine with the participation in the First Sacred War and the reorganization of the Pythie Games, but in the sixth century b. C. the attitude of the Pythia towards the tyranny was of hostility, as it also happened towards the Peisistratids in Athens and Polykrates in Samos during the same century.
Keywords: Oráculo de Delfos; Guerra; Delfos (Ciudad desaparecida)